2021
DOI: 10.1155/2021/9929128
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve the Efficiency of Transplantation with Mesenchymal Stem Cells for the Treatment of Ischemic Stroke: A Review of Recent Progress

Abstract: Cerebral ischemia is a common global disease that is characterized by a loss of neurological function and a poor prognosis in many patients. However, only a limited number of treatments are available for this condition at present. Given that the efficacies of these treatments tend to be poor, cerebral ischemia can create a significant burden on patients, families, and society. Mesenchymal stem cell (MSC) transplantation treatment has shown significant potential in animal models of ischemic stroke; however, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 134 publications
0
1
0
Order By: Relevance
“…Due to the promising safety profile of mesenchymal stromal cells (MSCs) in bloodborne diseases, coupled with the cells' multi-faceted therapeutic mechanisms, such as angiogenic, neurogenic, and vasculogenic, among other regenerative features, MSC transplantation for stroke has been translated from the lab to the clinic [24,25]. MSCs can influence the paracrine system to produce factors that promote microglia activation, increase astrocyte survival, and promote the bystander effect [25][26][27].…”
Section: Stem Cell-based Regenerative Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…Due to the promising safety profile of mesenchymal stromal cells (MSCs) in bloodborne diseases, coupled with the cells' multi-faceted therapeutic mechanisms, such as angiogenic, neurogenic, and vasculogenic, among other regenerative features, MSC transplantation for stroke has been translated from the lab to the clinic [24,25]. MSCs can influence the paracrine system to produce factors that promote microglia activation, increase astrocyte survival, and promote the bystander effect [25][26][27].…”
Section: Stem Cell-based Regenerative Medicinementioning
confidence: 99%
“…The inflammatory response following a stroke can be reduced by MSC's immunomodulatory effect, a main driving factor in functional recovery and patient outcomes [25]. MSC therapy is a frontrunner in a clinical setting since, as a vial therapy, it can be feasible, readily accessible, and safe for patients, as demonstrated by preceding clinical trials [24,25]. While preclinical models have shown efficacy, this has not carried over into clinical trials, leaving much to be discovered on MSC administration and viability [26].…”
Section: Stem Cell-based Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies showed that VCAM-1 is an angiogenesis-related marker [ 14 ] and that VEGF can activate the signal transduction pathways that regulate VCAM-1 expression [ 15 ]. Additionally, enhanced neovascularization and neurogenesis could be the essential mechanisms by which insulin-like growth factor-1 (IGF-1)/IGF-1R improves functional recovery after stroke [ 16 ].…”
Section: Introductionmentioning
confidence: 99%